(3QSGdI aj UaI GdESWQdGH HGdWQjb GdUfGYis - (3efUhQ Hf Ydj, CHh fUQ GHf YQGb , J fMh (B425 (3g`s
(3ChdgG (B:s
(3SQfi CWGd Gddg HbGA GdMQ GdcGed hGdfLjH GdaGVd eG hbaJ Ydjg ef QHZI di (B( (3GbJaGA (B) (3GdYdhe heMHI NGUI dYde GdfLhe Cf CQSe dg CjOg Gddg ai UfYJg YedGU NajakG eDOjkG Edi GdMbjbI s
(3BNQgG (B:s
(3agPG CjOc Gddg GdMQ GdaGVd ai UfYI GdGSWQdGH Yed Naja Ydi UMJg QSeJg dg RGOg Gdgd QZHI ai GdYde hHdZg GbGUi GeGfjI ajg Hefg hdWag JeJ GdQSGdI hddg GdMeO s
(3HYK GdeDda HgG Edi CHj YHO Gddg eMeO Hf Ydi GdeCehfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B846s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs